Political Law’s Reconstruction of Village Apparatus To Realize Independent Village in Indonesia - Hartati Hartati; Pahrudin HM; Elita Rahmi (Journal of Government and Civil Society, 2020)
Indonesian Village Law 2014 states that the purpose of village regulation is to create an independent village. Village management in Indonesia is carried out using a self-governing community system that requires apparatus that has good capacity. On the other hand, the existence of village apparatus in Indonesia still does not have the capacity needed to organize the government to become an independent village. Therefore, it is necessary to do a political law reconstruction to find a solution to the inequality of expectations of village regulation and the reality of the quality of village officials like this. Political law functions as a bridge to the goals to be achieved and is strongly influenced by the social reality of society. This research was conducted using a qualitative approach with the type of library research by reviewing data related to villages in Indonesia, especially village government. The results of this study revealed that only 7.43% were independent villages, most of village apparatuses unprofessional, poverty rate 9.66%, and unemployment rate of 5.01%. This requires a solution through a series of solution policies so that the objectives of village regulation towards independent villages can be achieved so that the prosperous community can be achieved.Undang-Undang Desa Tahun 2014 menyebutkan bahwa tujuan peraturan desa adalah untuk mewujudkan desa yang mandiri. Pengelolaan desa di Indonesia dilakukan dengan sistem kemasyarakatan swakelola yang membutuhkan aparatur yang memiliki kapasitas yang baik. Di sisi lain, keberadaan perangkat desa di Indonesia masih belum memiliki kapasitas yang dibutuhkan untuk menyelenggarakan pemerintahan menjadi desa yang mandiri. Oleh karena itu, perlu dilakukan rekonstruksi politik hukum untuk mencari solusi atas ketimpangan ekspektasi peraturan desa dan realitas kualitas aparatur desa seperti ini. Hukum politik berfungsi sebagai jembatan menuju tujuan yang ingin dicapai dan sangat dipengaruhi oleh realitas sosial masyarakat. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif dengan jenis studi pustaka dengan mengkaji data-data terkait desa di Indonesia khususnya pemerintahan desa. Hasil penelitian menunjukkan bahwa desa mandiri hanya 7,43%, perangkat desa sebagian besar tidak profesional, tingkat kemiskinan 9,66%, dan tingkat pengangguran 5,01%. Untuk itu diperlukan solusi melalui serangkaian kebijakan solusi agar tujuan peraturan desa menuju desa mandiri dapat tercapai sehingga masyarakat sejahtera dapat tercapai.